Structural and mechanical peculiarities of plastic deformation of (00l){100} Al single-crystal foils on flat Al alloy substrates under constrained cyclic tension; Physical Mesomechanics; Vol. 12, iss. 3-4, May-Aug. - Kuznetsov P. V. (2009, 2009)
The paper considers the structural and mechanical peculiarities of plastic deformation of {100}/00l\ Al single-crystal foils on flat Al alloy substrates in low-cycle fatigue. It is found that plastic deformation starts to evolve at the face of the foil after a latent period and propagates across the whole foil thickness as the number of loading cycles is increased. The relief formed on the back side of the Al foil is similar to that on its face. It is shown that the couple stresses arising in the foil cross-section in response to applied eccentric loads makes a major contribution to the origination of plastic strain at the face of the foil and its propagation across the whole foil thickness. It is concluded that the effect of couple stresses is to be taken into account in deposition of protective and functional coatings on foils, particularly where the coating thickness is large and the composition is operated under cyclic tension